Identifikasi Timbulan, Komposisi, Karakteristik dan Potensi Daur Ulang Limbah Padat Tanaman Hortikultura - Feby Reyna Putri; Yommi Dewilda; Rizki Aziz (Fakultas Teknik, 2023)
Solid waste produced by vegetable crops has the potential to cause environmental pollution because it has not been managed properly. Sampling is done by purposive sampling method and SNI provisions 19-3964-1994. Units of waste generation in weight and volume are consecutively 0.315 kg / m2/ harvest and 2,509 L/ m2/ harvest. The generation of waste in Tanah Datar Regency in units of weight and volume is consecutively 51.793,009 tons/year and 363.490,429 m3/ year. The composition of pre-harvest waste in the form of agricultural waste is 50%, dry waste is 27%, and hazardous and toxic substance waste 23%. Composition of post-harvest waste in the form of agricultural waste 100%. The average weight of waste type is 0.205 kg/ L, water content 35.479%, volatile levels 62.482%, ash levels 1.243%, fixed carbon 0.796%, C / N ratio 16,580, and biodegradability fraction 74.273%. The recycling potential of pre-harvest waste for LDPE plastic types is 2,437% and compostable organic waste is 50,116%. The post-harvest recycling potential is 100% in the form of compostable organic waste. Based on the results, the waste produced has the potential to be reused, recycled, and processed by third parties specifically for hazardous and toxic substance waste.